Primeval very low-mass stars and brown dwarfs: II. the most metal-poor substellar object - Zhang, Zeng Hua; Homeier, Derek (Monthly notices of the Royal Astronomical Society, 2017)
SDSS J010448.46+153501.8 has previously been classified as an sdM9.5 subdwarf. However, its very blue J − K colour (-0.15 ± 0.17) suggests a much lower metallicity compared to normal sdM9.5 subdwarfs. Here, we re-classify this object as a usdL1.5 subdwarf based on a new optical and near-infrared spectrum obtained with X-shooter on the Very Large Telescope. Spectral fitting with BT-Settl models leads to Teff = 2450 ± 150 K, [Fe/H] = -2.4 ± 0.2 and log g = 5.5 ± 0.25. We estimate a mass for SDSS J010448.46+153501.8 of 0.086 ± 0.0015 M⊙ which is just below the hydrogen-burning minimum mass at [Fe/H] = -2.4 (∼0.088 M⊙) according to evolutionary models. Our analysis thus shows SDSS J010448.46+153501.8 to be the most metal-poor and highest mass substellar object known to-date. We found that SDSS J010448.46+153501.8 is joined by another five known L subdwarfs (2MASS J05325346+8246465, 2MASS J06164006−6407194, SDSS J125637.16−022452.2, ULAS J151913.03−000030.0 and 2MASS J16262034+3925190) in a ‘halo brown dwarf transition zone’ in the Teff-[Fe/H] plane, which represents a narrow mass range in which unsteady nuclear fusion occurs. This halo brown dwarf transition zone forms a ‘substellar subdwarf gap’ for mid L to early T types.